2013
DOI: 10.1126/science.1232542
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Quantitative Enhancer Activity Maps Identified by STARR-seq

Abstract: Genomic enhancers are important regulators of gene expression, but their identification is a challenge, and methods depend on indirect measures of activity. We developed a method termed STARR-seq to directly and quantitatively assess enhancer activity for millions of candidates from arbitrary sources of DNA, which enables screens across entire genomes. When applied to the Drosophila genome, STARR-seq identifies thousands of cell type-specific enhancers across a broad continuum of strengths, links differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

45
1,196
4
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 955 publications
(1,309 citation statements)
references
References 47 publications
45
1,196
4
12
Order By: Relevance
“…Next, we compared the barcode reporter activity levels measured by CHEQ-seq to the existing multiplex enhancer-reporter method STARR-seq (Arnold et al 2013), using the same captured fragments and the same transfection conditions (Supplemental Figs. S9, S10; Supplemental Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we compared the barcode reporter activity levels measured by CHEQ-seq to the existing multiplex enhancer-reporter method STARR-seq (Arnold et al 2013), using the same captured fragments and the same transfection conditions (Supplemental Figs. S9, S10; Supplemental Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…S1A). These enriched DNA fragments, averaging 500 base pairs, are then cloned upstream of a fluorescent protein reporter preceded by a minimal promoter and a synthetic intron (Arnold et al 2013) and followed by a 17 base pair random barcode allowing for 17 × 10 9 possible barcodes (Methods). Using CHEQ-seq, we tested the enhancer activity of 1526 TP53 ChIP-seq peaks obtained in MCF7 breast cancer cells treated with Nutlin-3a (Janky et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recently several high-throughput enhancer screens (e.g. STARR-seq) (Arnold et al, 2013) have been reported. Similarly, more hi-C based datasets are also available for different cell types.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…STAP-seq is a clever inverse of the successful STARR-seq method 9 for probing enhancer activity developed by the same group. The authors construct a candidate libraryand use it to assess sequence-intrinsic core promoter strength and promoter potential of candidate regions that span the entire Drosophila genome (Figure 1a In the second paper, van Arensbergen et al 8 introduce SuRE, which similarly queries the autonomous promoter activity of random genomic fragments outside of their genomic context using a defined reporter assay.…”
mentioning
confidence: 99%